Brassinosteroid biosynthesis and signalling in Petunia hybrida - Verhoef, Nathalie (Journal of experimental botany, 2013)
Brassinosteroids (BRs) are steroidal plant hormones that play an important role in the growth and development of plants. The biosynthesis of sterols and BRs as well as the signalling cascade they induce in plants have been elucidated largely through metabolic studies and the analysis of mutants in Arabidopsis and rice. Only fragmentary details about BR signalling in other plant species are known. Here a forward genetics strategy was used in Petunia hybrida, by which 19 families with phenotypic alterations typical for BR deficiency mutants were identified. In all mutants, the endogenous BR levels were severely reduced. In seven families, the tagged genes were revealed as the petunia BR biosynthesis genes CYP90A1 and CYP85A1 and the BR receptor gene BRI1. In addition, several homologues of key regulators of the BR signalling pathway were cloned from petunia based on homology with their Arabidopsis counterparts, including the BRI1 receptor, a member of the BES1/BZR1 transcription factor family (PhBEH2), and two GSK3-like kinases (PSK8 and PSK9). PhBEH2 was shown to interact with PSK8 and 14-3-3 proteins in yeast, revealing similar interactions to those during BR signalling in Arabidopsis. Interestingly, PhBEH2 also interacted with proteins implicated in other signalling pathways. This suggests that PhBEH2 might function as an important hub in the cross-talk between diverse signalling pathways